2022
DOI: 10.1186/s11658-022-00348-2
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 gene editing: a new approach for overcoming drug resistance in cancer

Abstract: The CRISPR/Cas9 system is an RNA-based adaptive immune system in bacteria and archaea. Various studies have shown that it is possible to target a wide range of human genes and treat some human diseases, including cancers, by the CRISPR/Cas9 system. In fact, CRISPR/Cas9 gene editing is one of the most efficient genome manipulation techniques. Studies have shown that CRISPR/Cas9 technology, in addition to having the potential to be used as a new therapeutic approach in the treatment of cancers, can also be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 194 publications
0
40
0
Order By: Relevance
“…Studies on cellular and animal models have shown that the CRISPR/Cas9 technique can be effective in treating cancers [ 320 ]. For this reason, several clinical trials are underway to evaluate the efficiency of this technology in treating cancers [ 321 , 322 ]. While no treatment is available using this system, a recent study showed that decreasing MYCN copy number by using MYCN-A3 alkylating agent can down-regulate MYCN expression and suppress NB growth in vitro and in a xenograft mouse model [ 323 ].…”
Section: Mycn As Therapeutic Targetmentioning
confidence: 99%
“…Studies on cellular and animal models have shown that the CRISPR/Cas9 technique can be effective in treating cancers [ 320 ]. For this reason, several clinical trials are underway to evaluate the efficiency of this technology in treating cancers [ 321 , 322 ]. While no treatment is available using this system, a recent study showed that decreasing MYCN copy number by using MYCN-A3 alkylating agent can down-regulate MYCN expression and suppress NB growth in vitro and in a xenograft mouse model [ 323 ].…”
Section: Mycn As Therapeutic Targetmentioning
confidence: 99%
“…To further enhance our understanding of the evolution of drug resistance in cancer, technologies, such as CRISPR/Cas, clonal tracing, or spatial analyses, can be applied to experimental evolution. The CRISPR/Cas system can be used to characterize potentially different mechanisms of resistance against a drug [ 73 ]. For instance, this could be applied to the Ewing’s sarcoma experiment described above.…”
Section: Predicting Drug Sensitivity To Improve Treatment Planningmentioning
confidence: 99%
“…Gene editing can also serve as a therapeutic tool for reducing chemoresistance by knocking in or knocking out associated genes. Gene editing as an approach to overcome drug resistance has been thoroughly reviewed elsewhere [ 224 ]. Briefly, total removal of a gene correlated to resistance would provide more of a long-term response in comparison to RNAi-based therapies and has been shown to provide therapeutic benefits in ovarian cancer.…”
Section: Clinical Relevance and Future Directionsmentioning
confidence: 99%